Investigating Asset Governance Mechanisms in a Proprietary Software Ecosystem - Costa, Luiz Alexandre; Fontao, Awdren Lima; Santos, Rodrigo Pereira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2020.13769, 2020)
The reuse of artifacts generated throughout the proprietary software development has been improved to support and promote relationships among vendors, consumers and a central organization that maintains the common technological platform. This scenario has been investigated as Software Ecosystems (SECO). When the ecosystem is centered in a closed platform, it is known as a proprietary SECO. In this case, establishing software asset management policies and guidelines is a critical aspect for maintaining a sustainable SECO. Contributions from actors that are external to the central organization should be allowed without exposing internal knowledge and risking the ecosystem robustness of the ecosystem. In this context, this study investigates asset governance mechanisms in a proprietary SECO by: (1) a survey research with 34 participants to capture insights on some mechanisms, (2) a set of 8 interviews with a group of managers to analyze the most relevant mechanisms; and (3) a correlation analysis from the managers’ opinions.